Akuntabilitas Pengelolaan Alokasi Dana Desa (Studi Kasus Di Desa Karangrejo Kecamatan Gumukmas Kabupaten Jember Tahun 2017) - Maghfiroh Noviandari; Diyah Probowulan; Astrid Maharani (Ecobuss, 2018)
This research aims to evaluate the management accountability of Village Fund Allocation which consists of planning, implementation, administration, reporting, and accountability conducted by Karangrejo Village, Gumukmas Subdistrict, Jember Regency in 2017. This research is a qualitative research through a preliminary survey to the object of research, interview, and documentation . The results of this study indicate that the management of Village Fund Allocation in Karangrejo Village is accountable and transparent in the planning, implementation, administration, reporting, and accountability stages. Village Fund Allocation planning is evaluated through discussion forum at the village level. Disbursement of procedures and distribution of Village Fund Allocation is in accordance with the rules of Jember Regent's Regulation No. 39 of 2017. Accountability report of the Village Fund Allocation implementation realization is integrated with APBDes accountability. Also supported by people who actively participate in rural development. Keywords: Accountability, Allocation Fund Village, Management, Transparency